New antenna layout for a SuperDARN HF radar. Issue 6 (12th December 2013) - Custovic, Edhem; McDonald, Andrew J.; Whittington, James; Elton, Darrell; Kane, Thomas A.; Devlin, John C.
<x xml:space="preserve">Abstract</x> [1] A new antenna layout for a Super Dual Auroral Radar Network (SuperDARN) HF radar has been developed. The new layout utilizes two auxiliary arrays; one behind and one in front of the main array, rather than the single auxiliary array that existing radars use. The rear auxiliary array consists of three antennas providing beam‐steering capability while the front auxiliary array consists of a single antenna. This layout is expected to greatly improve the calculation of elevation angle of arrival. Simulations presented show the advantages and disadvantages of using twin‐terminated folded dipole (TTFD) antennas and log‐periodic dipole arrays in standard and modified SuperDARN array configurations. TTFD antennas are shown to have superior front‐to‐back ratio and beam‐steering capability but suffer from shadowing effects due to the presence of corner reflectors. Impedance‐matching techniques used in SuperDARN radars are discussed, and the results of a new matching method, exhibiting a superior voltage standing‐wave ratio over the SuperDARN frequency band, are presented. Shadowing of the main array by the front auxiliary array is investigated, and it is shown that the impact of the front array on the main array gain pattern is significantly less for the case of a single front antenna than for a four‐antenna front array. Radar phase calibration techniques are discussed, and it is proposed that the additional single‐antenna front array be used for system‐wide radar phase calibration. An algorithm for the determination of elevation angle of arrival using the new layout is also given.